Saksi Sedarah Dalam Perkara Pidana - Hanisa Sokanfuti; Elsa Rina Maya Toule; Judy Marria Saimima (PATTIMURA Law Study Review, 2023)
Law enforcement is an effort to turn ideas and concepts into reality. Enforcement is the process of realizing the will of the law. The legal will referred to here is the expression of the legislator's thoughts in legal provisions. Discussions about the law enforcement process also extend to lawmaking. The formulation of the legislator's thoughts as outlined in the provisions of the law will also determine how it will be enforced. This research is normative juridical research. This type of research is descriptive analysis. The supporting data and information are then identified and then systematized for interpretation and arguments are given to reach a conclusion on the problem. The results of the research show that there are doctrines or theories of criminal responsibility for domestic violence, so for law enforcement officers in Indonesia there should no longer be any legal problems in filing a case as a suspect or defendant in the Indonesian criminal justice system, as long as this is justified by legislation (e.g. domestic violence legislation). The position of a witness who is related to the defendant or is a qualified witness is categorized as providing testimony without oath if they give their statement at trial without the consent of the defendant and the public prosecutor. The position of children as witnesses in criminal cases is recognized and legal in the Criminal Procedure Code, but based on the legislation, children cannot be held accountable in criminal law, so children cannot be sworn in to provide information, therefore the information is only used for guidance or as additional legal evidence. and strengthen the judge's confidence.